Compositional Technique as a Tool of Political Statement in the Works of Louis Andriessen - Vyshynskyi, Vitalii (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
Relevance of the study. The work of Louis Andriessen, a Dutch composer, is regarded as a significant contribution to the formation of music culture of the second half of the 20th century. Despite his influence, however, there are practically no research papers in domestic musicology that would analyze Andriessen’s work and personality or his professional musical and political activities. One of the main research topics related to Andriessen’s work is the influence of politics on music. The topic itself is quite particular and somewhat controversial because it always leaves a lot of questions that need further clarification, may require a different perspective and a new approach. One of such questions with a controversial view is a discussion of how compositional techniques can be influenced by and formed based upon the composer’s political views. Main objective of the study. Taking into consideration Louis Andriessen’s own experiences, analyze how his compositional techniques created political content of his works, and particularly the writing of the cantata “De Staat” (“The Republic”) by Plato. Methods. The following were used in the research analysis: biographical (in the analyses of the style and work of the composer); historical (in the analyses of the cultural and socio-political context); comparative (in the analyses of the political and aesthetic views and standpoints of artists); analytical (in the analyses of the musical works). Results/findings and conclusions. There were several reasons that led Louis Andriessen to appeal to minimalism. The main reason was the composer’s desire to respond to his fellow composers that themselves were searching for their own applicable techniques and style to disseminate political ideas. Minimalism was particularly attractive to the composer because it was relevant, easily accessible to the general public, and reflective. At the same time, it was politically appropriate and democratic. The musical and political activism of Andriessen was aimed at creating a new type of communication and relationships between a composer and a performer, a performer and audience, and ultimately at creating a new musical community. This new type of communication and community is reflected in the composer’s work “The Republic”. For performers in particular, “The Republic” became a practical exercise similar to the style of Lehrstück B. Brecht, which allowed performers to adapt to new musical interactions proposed by the composer. Andriessen was able to achieve this goal by using hocket techniques — i. e., by removing the role inequality among performers and emphasizing the expressive importance of each performer in a musical composition. However, Andriessen’s compositional techniques used in “The Republic” to reflect his political views did not support, but rather emphasized the composer’s contradictory political position and in particular his binary position to Plato’s views on the place of music in politics. Nevertheless, it was “The Republic” that started the creation of a unique performance and approach in musical composition called “Andriessen’s approach”, which would successfully combine minimalism with traditional European compositional techniques, modern and experimental techniques, and components of music at large. At the very end, the unique combination of the aforementioned compositional techniques is what identifies the specificity of the content of Andriessen’s music. Significance of these results consists in the point of view on the question of how a compositional technique forms political content in the music written by Louis Andriessen